Learning About Identity Through Bipolar Disorder and Learning about Bipolar Disorder Through Identity - Arase, Sophie (2024)
In this paper, I discuss bipolar disorder (BD) and identity. My general goal is to argue that working on BD and identity from a philosophical, interdisciplinary perspective has promise to be beneficial for empirical research on the topic, for people with BD, and for philosophical treatment of identity. I first argue that both people with BD and empirical researchers on the topic of BD and identity implicitly understand "identity" as it is understood in (some areas of) philosophy. Namely, as identity in the characterization sense and, often, specifically as practical identity. I call this conception of identity "characterization-identity". If this is the case, then empirical researchers have more data to work with when trying to understand why people with BD experience particular difficulties with identity: they can appeal to the extant work on characterization-identity. Having argued that the researchers and people with BD understand "identity" in this way, I move to making the case that, insofar as we have a sound account of characterization-identity, this method of research has the potential to be mutually beneficial: (1) Work on characterization-identity can explicate the empirical work on, and first-hand experience of, BD and difficulty with identity. (2) The empirical work and first-hand accounts suggest a desideratum for a good account of identity. And (3) the interdisciplinary treatment of the topic could generate therapeutic interventions for people with BD.